ADAPTASI DIRI PADA LANSIA DI PANTI WERDHA MOJOPAHIT MOJOKERTO - Dwi Harini Puspitaningsih Duduk Adi Prasetyo (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2014)
The fact that happens in Panti Werdha Mojopahit Mojokerto is the social problems, such as many people who live inside are often alone and rarely out with their friend and also they look uncomfortable living in panti werdha because they can’t adjust their selves in their environment of panti. The purpose of this study is to know the overview of self adaptation to elderly in Panti Werdha Mojopahit Mojokerto. Design of this study is descriptive with survey. The variabel of this study is self adaptation to elderly. The population of this study is all of elderly in Panti Werdha Mojopahit Mojokerto amount 37 elderly. The sampling taken with technique of total sampling amount 37 respondents. Data collected with questionnaire and processed by coding, editing, scoring and tabulating and presented in from of a frequency distribution table. Results of the study showed that most respondents have a negative self adaptation amount 22 respondents (59,5%) and a positive self adaptation amount 15 respondents (40.5%). The result analysis of overview self adaptation to elderly in Panti Werdha Mojopahit Mojokerto using a likert scale changed to score T. it will be positive the result of if score T is > 50 and it will be negative if the result of score T is < 50. The results of this study showed that the elderly who live in panti werha have the pressure from the internal environment and make uncomfortable between elderly inside and quarrel between them. So many elderly who haven’t yet adjust their personality and sosical adaptation are more increased the environment in Panti Werdha Mojopahit. Coaching and councelling are more increased make the elderly to undergo their life and be able to adapt well.